Аналіз стану розвитку теплогенеруючих джерел систем теплопостачання в Україні за 2000–2007 роки - Kuts G.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2010)
The analysis of change of the state of heat-generating sources is conducted in the heat supply systems of Ukraine for period 2004–2007 years. Development of heating boiler-rooms which in general annual volume of the released thermal energy had a stake at the level of 60–63 % is considered in detail. During the noted years the amount of heating boiler-rooms grew on 20 %. This growth happened mainly due to putting into the operation of heating caldrons by single power to 3 MW. As a result the percent of decentralization was increased on the whole on a country on 4,0 %, in city settlements – on 4,5 %, in rural locality – on 2,5 %. In fuel balance of heating boiler-rooms the basic type of fuel is natural gas, level of which in a general volume 85,5 % made on the state 2007. The actual discharge intensity of conditional fuel on distribution of thermal energy made 169–170 of kg conditional fuel /giga calorie. This index, as compared to 2000, went down only on 1,0 of kg conditional fuel /giga calorie. The process ofupdate fleet of boiler-rooms goes unsatisfactory rates. So, on the state 2007, amount of boiler-rooms with the term of exploitation 23,7 % made over 20 years, and the extent of decrepit and emergency thermal networks in a double-pipe calculation makes a 518,4 km, that is evened 14,5 % from their general extent.